Rozumowanie dedukcyjne w procesie uczenia się języka niemieckiego jako drugiego języka obcego na przykładzie podsystemu gramatycznego - Bawej, Izabela (Neofilolog, 2022)
The role of the first foreign language in second foreign language learning is an interesting research question. The main purpose of the research was to relate if and how the learners make deductions about German grammar based on English language skills. Therefore, this study presents the results of a survey conducted among students of Applied Linguistics who learn German after English. Participants were interviewed to state their opinion about the usefulness of English in learning German structures. The results of this inquiry allow the conclusions that learners use and transfer the previously acquired knowledge and information from what they have in first foreign language in order to understand, learn or form structures in the second foreign language. They compare both languages, look for similarities in the creation of the construction and the application of the structures or constructions, conclude by analogies between English and German in grammatical subsystem. In this way they deduce that English makes possible and facilitates to memorize grammatical forms while learning German, e.g. passive voice, articles, tenses, irregular verbs, comparative and superlative adjectives.